The Dualism of Court Institutions: Challenges in Harmonizing the National Legal System (Indonesian Court and Justice Review, 2025)
Indonesia’s judiciary is characterized by institutional dualism, with multiple court jurisdictions—general, religious, military, administrative—operating under a decentralized and often fragmented legal framework. This structural dualism presents ongoing challenges in achieving coherence, consistency, and legal unity. This study explores the implications of such institutional fragmentation for legal harmonization and judicial efficiency. Through a doctrinal and comparative legal analysis, combined with field interviews and policy reviews, the research investigates areas where overlapping jurisdiction, conflicting procedural norms, and divergent judicial training contribute to inconsistency in legal interpretation and public confusion. The findings show that, although the integration of judicial administration under the Supreme Court was a step toward unification, substantive harmonization remains elusive. This has led to jurisdictional conflicts, especially in areas such as family law, land disputes, and administrative oversight. The novelty of the study lies in its critical appraisal of judicial dualism from both structural and functional perspectives. It argues that harmonization efforts must go beyond administrative integration and address deeper issues of legal culture, normative hierarchy, and cross-jurisdictional jurisprudence. This research offers recommendations for improving coordination across courts, standardizing procedural rules, and fostering a more unified national legal identity. As Indonesia continues to develop its legal infrastructure, addressing judicial dualism is vital to enhancing legal certainty and access to justice.